2015
DOI: 10.4103/1658-354x.152839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute physiology and chronic health evaluation II and Glasgow Coma Score in predicting the outcomes of Post Anesthesia Care Unit′s patients

Abstract: Context:Acute physiology and chronic health evaluation II (APACHE II) is one of the most general classification systems of disease severity in Intensive Care Units and Glasgow Coma Score (GCS) is one of the most specific ones.Aims:The aim of the current study was to assess APACHE II and GCS ability in predicting the outcomes (survivors, non-survivors) in the Post Anesthesia Care Unit's (PACU).Settings and Design:This was an observational and prospective study of 150 consecutive patients admitted in the PACU du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In the eye response component of the FOUR scale, a complete score is awarded only when the patient can blink ondemand or follow a target, which helps make a distinction between the aforementioned states12,22 . Despite all these shortcomings of GCS, Hosseini et al reported that this scale was even better than APACHE II in predicting patient mortality23 . Cho et al stated that although GCS is suitable for assessing early mortality, it is not a good replacement for APACHE, as APACHE II is a better predictor of late mortality24 .…”
mentioning
confidence: 99%
“…In the eye response component of the FOUR scale, a complete score is awarded only when the patient can blink ondemand or follow a target, which helps make a distinction between the aforementioned states12,22 . Despite all these shortcomings of GCS, Hosseini et al reported that this scale was even better than APACHE II in predicting patient mortality23 . Cho et al stated that although GCS is suitable for assessing early mortality, it is not a good replacement for APACHE, as APACHE II is a better predictor of late mortality24 .…”
mentioning
confidence: 99%
“…In a study by Hosseini et al . using a cut‐off score 13·5, The APACHE II score predicted hospital mortality with a sensitivity of 96·6%, a specificity of 62·8% and accuracy of 79·7%, with an area under the ROC curve of 0·857 (Hosseini and Ramazani, ). In another study by Fadaizadeh et al, a total of 415 records of patients admitted during a 1‐year period were retrospectively reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…To generate risk estimates in accordance with the observed outcomes at different classes of risk, model calibration should be assessed; in other words, calibration power of the model represents the agreement between individual probabilities and actual outcomes. Using the Hosmer-Lemeshow goodness of fit (GOF), P value > 0.05 indicates a well-calibrated model (17). Also, the STROBE checklist was used to guide the reporting of the study.…”
Section: Methodsmentioning
confidence: 99%